2021
DOI: 10.3390/ijms22147537
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of the Polycomb Group Family in Medicago truncatula

Abstract: Polycomb group (PcG) proteins, which are important epigenetic regulators, play essential roles in the regulatory networks involved in plant growth, development, and environmental stress responses. Currently, as far as we know, no comprehensive and systematic study has been carried out on the PcG family in Medicago truncatula. In the present study, we identified 64 PcG genes with distinct gene structures from the M. truncatula genome. All of the PcG genes were distributed unevenly over eight chromosomes, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 117 publications
0
8
0
Order By: Relevance
“…These cereal E(z) homologs are orthologs of Arabidopsis CLF and SWN, and the Su(z)12 homologs fall into the EMF2 clade [ 49 ]. A recent study in M. truncatula identified 31 PRC2 core components, containing two MEA ortholog and one VRN2 ortholog [ 24 ], which is distinct from those in cereals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These cereal E(z) homologs are orthologs of Arabidopsis CLF and SWN, and the Su(z)12 homologs fall into the EMF2 clade [ 49 ]. A recent study in M. truncatula identified 31 PRC2 core components, containing two MEA ortholog and one VRN2 ortholog [ 24 ], which is distinct from those in cereals.…”
Section: Discussionmentioning
confidence: 99%
“…The orthologs of Arabidopsis MEA and FIS2 are also absent in cotton species, in line with that in cereals [ 17 20 , 23 ]. Nevertheless, the VRN2 orthologs have been identified, similar to M. truncatula [ 24 ]. Unsurprisingly, different cotton PRC2 members of the same clade display good collinearity, identical gene and protein structures, and similar subcellular localizations (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the NF-YB subfamily plays key role in improving drought tolerance in plants such as Arabidopsis [13], tobacco [18], and maize [19]. Gene families such as P450 [23], HD-ZIP [24], SRS [25], and PcG [26] in Medicago have been identified. These families are related to abiotic stress and growth, but the NF-YB gene family has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%